2017
DOI: 10.1021/acs.molpharmaceut.7b00310
|View full text |Cite
|
Sign up to set email alerts
|

Click Biotinylation of PLGA Template for Biotin Receptor Oriented Delivery of Doxorubicin Hydrochloride in 4T1 Cell-Induced Breast Cancer

Abstract: PLGA was functionalized with PEG and biotin using click chemistry to generate a biotin receptor targeted copolymer (biotinylated-PEG-PLGA) which in turn was used to fabricate ultrafine nanoparticles (BPNP) of doxorubicin hydrochloride (DOX) for effective delivery in 4T1 cell induced breast cancer. However, adequate entrapment of a hydrophilic bioactive like DOX in a hydrophobic polymer system made of PLGA is not usually possible. We therefore modified a conventional W/O/W emulsion method by utilizing NHCl in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…The transformation of lutein from crystalline to amorphous form is important, as amorphous forms are characterized by higher solubilities and increased bioavailability [ 51 , 52 , 53 , 54 ]. Similar results (loss of characteristic peak) were observed in other studies where crystalline drugs such as SN-38, doxorubicin oxcarbazepine, prilocaine, and adefovir were encapsulated into PLGA-based micro- and nanoparticles [ 24 , 25 , 55 , 56 , 57 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The transformation of lutein from crystalline to amorphous form is important, as amorphous forms are characterized by higher solubilities and increased bioavailability [ 51 , 52 , 53 , 54 ]. Similar results (loss of characteristic peak) were observed in other studies where crystalline drugs such as SN-38, doxorubicin oxcarbazepine, prilocaine, and adefovir were encapsulated into PLGA-based micro- and nanoparticles [ 24 , 25 , 55 , 56 , 57 ].…”
Section: Resultssupporting
confidence: 87%
“…Thus, it is known that biotinylated prodrugs and polymeric nanoparticles utilize the SMVT and biotin transporters for enhanced permeability of drugs [ 19 , 23 ]. Moreover, scientists have reported that biotin-decorated polymeric nanoparticles have enhanced the uptake of poorly soluble drugs such as doxorubicin [ 24 ], SN-38 [ 25 ], and 15,16-dihydrotanshinone [ 26 ]. Therefore, we hypothesize that lutein-loaded PLGA–PEG–biotin polymeric nanoparticles can enhance the uptake of lutein into the retinal cells through SMVT transport system.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is widely used to antitumor agent design both in case when the targeting moiety is a low molecular weight compound (folate, carbohydrate residues, vitamins etc.) [147,194,254] or a protein (transferrin, growth factors) [131,255].…”
Section: Active Targetingmentioning
confidence: 99%
“…40 In the past decade, biotin was used as a targeting ligand for the delivery of various anti-cancer drugs, e.g., platinum, ferrocene, paclitaxel and doxorubicin, to tumors. 4144…”
Section: Resultsmentioning
confidence: 99%